Junge Szene Wien '91. - Rakuschan, F.E (Wien : Wiener Secession, 1991)
Beck, Martin ; Bernatzik, Bernard ; Degenhardt, Carla ; Melkonyan, Elisabeth ; Eckert, Eva ; Fleissner, Richard ; Grübl, Elisabeth ; Jakob, Beate ; Koller, Günter ; Leupold-Löwenthal, Daniela ; Lindner, Lydia ; Nebel, Christoph ; Öllinger, Michael ; Posch, Johannes ; Rohrmoser, Wolfgang ; Sommerer, Christa ; Streit, Christoph ; Trauttmansdorff, Okavian ; You neever know ; Zinner, Birgit
Junge Szene Wien '91, Wiener Secession, Wien, 14. August - 22. September 1991
Duits
kunstcatalogus
Keywords: Wenen